Edible landscape: Key factors determining consumers’ commitment and willingness to accept opportunity cost and risk of foraged food - Rombach, Meike; Dean, David (Frontiers in Horticulture, 2023)
This study is dedicated to urban foraging and explores key factors that determine consumer willingness to try foraged food, willingness to spend time and effort, accept risk as well as make a commitment towards food foraging, using partial least square structural equation modelling. Results emphasize that the strongest driver of willingness to try are the approval of responsible food foraging activities and the individual benefits of food foraging. For the willingness to spend extra time and effort, all the predictors have some impact. In terms of willingness to accept risk, approval of responsible food foraging activities and the societal benefits of food foraging are influential. For commitment to food foraging, the individual and societal benefits are the most important key-drivers. These findings are of relevance to marketing managers in the food industry and gastronomy, as well as municipalities, landscape designers and horticultural businesses.